2022
DOI: 10.1002/hbm.26122
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of neurovascular decoupling and cognitive impairment in patients with end‐stage renal disease during a hemodialysis session: Evidence from a comprehensive fMRI analysis

Abstract: Neurovascular (NV) decoupling is a potential neuropathologic mechanism of cognitive impairment in patients with end‐stage renal disease (ESRD). Hemodialysis improves cognitive impairment at 24 h post‐dialysis, which suggests a potential neuroprotective effect of hemodialysis treatment on the brain. We investigated the effects of hemodialysis treatment on the reversal of NV decoupling associated with cognitive improvement. A total of 39 patients with ESRD and 39 healthy controls were enrolled. All patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Statistical analysis was performed using SPSS 25.0 software. The paired samples t-test was used to compare the preoperative and postoperative groups, while the independent samples t-test was used to compare the preoperative and postoperative groups with healthy controls (Li et al, 2023). Categorical variables were analyzed using the chi-square test.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was performed using SPSS 25.0 software. The paired samples t-test was used to compare the preoperative and postoperative groups, while the independent samples t-test was used to compare the preoperative and postoperative groups with healthy controls (Li et al, 2023). Categorical variables were analyzed using the chi-square test.…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly evident that dysfunction and damage within the cerebral microcirculation constitute significant contributors to age-related cognitive decline [17,29,[273][274][275][277][278][279]. Clinical investigations have furnished evidence suggesting that the consumption of a methionine-rich diet, coupled with hyperhomocysteinemia, can incite dysregulation in cerebral blood flow, directly impacting cognition [280][281][282][283]. Experimental studies have extended these clinical observations, providing valuable mechanistic insights into the synergistic interplay between the aging process and diet-induced accelerated cellular aging, particularly concerning cerebromicrovascular function [173,178,284].…”
Section: Methionine-rich Diet and Vascular Contributions To Cognitive...mentioning
confidence: 99%
“…Endothelial dysfunction induced by high-methionine diets or hyperhomocysteinemia can further disrupt neurovascular coupling by impairing the dilation of cerebral arterioles in response to neuronal activation [281,318]. Clinical and preclinical studies have reported associations between high methionine intake or hyperhomocysteinemia, dysregulation of cerebral blood flow, and cognitive dysfunction [173,178,280,[282][283][284]319].…”
Section: Endothelial Dysfunction and Dysregulation Of Cerebral Blood ...mentioning
confidence: 99%
“…Thus, the spatial correlation between CBF and a measure of local brain connectivity has been proposed as a surrogate index for NVC. Several studies have assessed NVC using two different indices, namely, the correlation between ASL and resting‐state functional magnetic resonance imaging (rs‐fMRI) at the global level and the ratio of perfusion and neural activity or brain connectivity at the regional level (Li et al., 2022 ; Li et al., 2023 ; Liang et al., 2013 ; Shang et al., 2022 ; Zhu et al., 2017 ). For example in a recent study, they investigated the four types of NVC between amplitude of low‐frequency fluctuation (ALFF), fractional ALFF, regional homogeneity, degree centrality, and CBF, and indicated that ESRD patients showed NVC dysfunction in global gray matter and multiple brain regions due to the mismatch between CBF and neural activity (Hu et al., 2024 ).…”
Section: Introductionmentioning
confidence: 99%